Education for employability. - Higgs, Joy; Letts, William J., 1965-; Crisp, Geoffrey (Practice futures, 2019)
We often look back at changing trends in higher education and call them "bandwagons" (temporary fads that everyone rushes to be part of and "jump on"). While much of the hype and jargon of "The Employability Agenda" may fade from the tip of our tongues (or perhaps be subsumed into the norm) in the mid future, there are two fundamental changes that will not: the digital revolution embedded in changing work and economic practices and the "re-globalisation" of the world that this and other politico-economic changes have brought about. These will continue to be part of how we live and work, so tertiary education will need to take its part in supporting employ-ability far beyond either the timing or scope of preparation for initial employment. Employability is important to local, national and international labour market contexts, parameters and policies. As well as impacting workforces, employability is an essential characteristic of workers. It is very important that employability is understood and enacted as personal employability not just employment of individuals. We have found that employability is defined as much, if not more, by mindset rather than skillset. Part of this mindset involves recognising the unknowns of future work and an even bigger part is recognising our responsibilities as workers and educators lies in shaping our own employability and that of the novice learners and workers in our spaces of influence and communities of practice. In Education for Employability (Volume 2): Learning for Future Possibilities we continue on from the big agenda discussions of Education for Employability (Volume 1): The Employability Agenda to explore education for employability in a variety of spaces: in the context of higher education as an entrance into the workforce, in joining communities of practice and in the lifelong pursuit of employability - preparing people for a portfolio of careers rather than a job-for-life. These two books show how educational leaders, educators, industry partners and thought leaders are imagining and addressing the challenges posed by the current and future changes facing our work, practices and workplaces.